SISTEM INFORMASI PENGELOLAAN ZAKAT PADA MASJID AR-RIDLWAN KOTA BEKASI - Samian, Tarmudi (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2020)
The research objective was to develop a zakat management system which was motivated by the inefficiency of the system in the Ar-Ridlwan Mosque Bekasi on the system, zakat management, muzakki data management, mustahik data management and other system management. It was expected that this application could help zakat management system more efficiently. This zakat management system was developed using java and it was expected that this application would be useful for mosques in the future. The design of zakat management system using java was carried out by the waterfall method. This method included system analysis, system design, system development, system testing, and implementation. The test results showed that this application provided convenience to mosque administrators, especially in the field of zakat management in the Ar-Ridlwan Mosque. Mosque administrators also found it easy to input all muzakki and mustahik data because this system was built using java which was indeed very easy to understand and use in zakat management. Based on the results of the study, the author could provide a proposed system and java-based desktop application and use MySQL about the information system that was adjusted to the research setting.